Perspectives on poverty in India (New Delhi, 2011)
The ongoing debate over poverty in India-its extent, trends, causes, and cures-is complex and often controversial. In recent decades, because difficult measurement issues have arisen, a disproportionate amount of attention has been devoted to assessments of the extent of poverty and the rate of poverty decline. Much less is known about how India's rapid economic expansion has altered the underlying poverty profile and how this affects the consequent search for its causes and cures. Perspectives on Poverty in India: Stylized Facts from Survey Data seeks to fill this gap. The book asks how India's structural transformation-from rural to urban and from agriculture to non-farm sectors-is impacting poverty and social exclusion. The analysis is significant in light of the fact that India faces considerable challenges in moving to the next generation of reforms, sustain growth, and expand the benefits of rapid growth across sectors, regions, and people.
Keywords: Poverty-India